Imāmī Thought in Iran during the Ilkhanid Period : The Ḥimṣī Rāzī Family - Ansari, Hassan (Middle East and Islamic Studies E-Books Online, Collection 2025., 2025)
Scholars studying the development of Imāmī thought are confronted with a lack of sources. Many pertinent works by Imāmī thinkers who lived in the various centers of Shīʿī learning between the lifetimes of al-Murtaḍā (d. 1044) and Naṣīr al-Dīn al-Ṭūsī (d. 1274) have not come down to us. Muʿtazilite thought, Avicennan notions, and the quest to return to the early doctrines of the imams constituted the principal parameters of Imāmī theological thought over those centuries. The present study, focussing on the Ḥimṣī Rāzī family, which flourished in Iran during the thirteenth and fourteenth centuries, showcases what can be achieved by gathering and piecing together relevant paratextual material that is preserved in manuscripts, providing insights into the scholarly profiles of its members. It is complemented by an editio princips of Mishkāt al-yaqīn, and a facsimile edition of the Talkhīṣ al-maqāṣid.